HUBUNGAN LINGKUNGAN KERJA DENGAN KEPUASAN KERJA KARYAWAN (KASUS BAGIAN PENGOLAHAN PT. SURYA BRATASENA PLANTATION KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN) - Iin Murtafia; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study was to determine The Relationship Work Environment WithEmployee Job Satisfaction (Case Proccessing Part PT. Surya Bratasena PlantationDistrict Of Pangkalan Kuras Pelalawan). This research is located in PT. SuryaBratasena Plantation. Which is located in the village of Sorek Districts Drain BasePelalawan. This research population is all employess at PT. Surya BratasenaPlantation processing section numbering 42 people. Data analisis in this study usingSPSS. Sampling technique is a method used census data and testing techniques usedin this study include validity test validitas, test reliabilitas, analysis korelasi spearmanand uji-t to test and prove the research hypothesis.The analysis showed that the working environment has a significantrelationship with job satisfaction of employees processing section PT. SuryaBratasena Plantation. Based on the results obtained by the value of r (correlationcoefficient) of 0,705% means that 70,5% of employee satisfaction variable processingsection PT. Surya Bratasena Plantation related to the work environment. The resultsof hypothesis testing found that t-count larger than t-table which means Ha accepted.Keywords : Work Environment, Job Satisfaction